Detection of NS1 antigen, IgM antibody for the diagnosis of dengue infection in patients with acute febrile illness - Neralwar, Arvind; Banjare, Bimala; R., Barapatre (International Journal of Research in Medical Sciences, 2017)
Background: Dengue is an endemic viral disease affecting tropical and subtropical regions around the world. Infection with any 1 of 4 dengue viruses produces with spectrum of clinical illness ranging from a mild undifferentiated febrile illness to dengue fever (DF) to dengue haemorrhagic fever (DHF), a potentially life threatening disease. The mortality and morbidity of DHF can be reduced by early diagnosis, hospitalisation and careful supportive care. Detection of non-structural antigen (NS1 Ag), IgM and IgG antibody may help in the early diagnosis. Methods: The present study was taken from the Pt J N M Medical College, Raipur (CG.) department of Microbiology. The one year study from August 2014 to July 2015 detection of NS1 Ag and IgM antibody. Elisa were tested a penal compared of 1637 serum specimens collected from acute febrile patients. Out of 1637 patients 538_were found to have acute dengue infection by detection of NS1Ag and anti-dengue IgM Elisa. Results: Out of 1637 patients 538- were found to acute dengue infection. Out of 538– NS1 161—IgM 294 positive. Males are more affected than females and 21 to 30 year age group were more infected. Dengue illness were more in rainy and post rainy season. Conclusions: The present study showed that dengue serological tests have a significant role in the early diagnosis of dengue fever, Hence, it is recommended to do the serological tests (NS1 Ag, IgM, IgG Ab) early in all suspected dengue cases so that, we can diagnosis early and initiate necessary treatment.